Determination of optical band gap of ZnO:ZnAl2O4 composite semiconductor nanopowder materials by optical reflectance method - Aydin, C.; Benhaliliba, M.; Al-Ghamdi, Ahmed A.; Gafer, Zarah H.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2013)
ZnO:ZnAl2O4 composite semiconductor nanopowder materials were synthesized by sol gel method. X-ray diffraction results reveal that Al doped ZnO samples have a polycrystalline hexagonal structure with a = 3.2506 , c = 5.2079 lattice parameters. The crystallite size of the ZnO samples is decreased with increasing Al content. Atomic force microscope results indicate the presence of micro/nanohexagons with different sizes from 128 to 166 nm. Optical band gap of the ZnO samples is decreased and reaches a low value of 2.82 eV for 20 % Al. The electrical conductivity dependence of temperature confirms that ZnO:ZnAl2O4 composite semiconductor nanopowder materials exhibit semiconductor behavior.
Keywords: ZnO nanomaterials; Sol gel route; Semiconducting properties